2021
DOI: 10.7150/thno.63860
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations for quantitative clinical SPECT/CT imaging of alpha particle emitting radioisotopes

Abstract: Rationale: Alpha particle emitting radiopharmaceuticals are generating considerable interest for the treatment of disseminated metastatic disease. Molecular imaging of the distribution of these agents is critical to safely and effectively maximize the clinical potential of this emerging drug class. The present studies aim to investigate the feasibility and limitations of quantitative SPECT for 223 Ra, 225 Ac and 227 Th. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Similarly to our findings with 212 Pb, they achieved quantitation of 5.6 ml volumes with an error smaller than 19% [43]. The count rate achieved with 212 Pb with the 79 keV energy window was much higher than when imaging 223 Ra [4,6,13,43]. However, a lot of photons contributing to the 79 keV energy peak are characteristic X-rays from the lead collimator and scattered photons from the 2.6 MeV emission of 208 Tl, and hence it would be more relevant to report the number of primary photons detected to compare sensitivity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly to our findings with 212 Pb, they achieved quantitation of 5.6 ml volumes with an error smaller than 19% [43]. The count rate achieved with 212 Pb with the 79 keV energy window was much higher than when imaging 223 Ra [4,6,13,43]. However, a lot of photons contributing to the 79 keV energy peak are characteristic X-rays from the lead collimator and scattered photons from the 2.6 MeV emission of 208 Tl, and hence it would be more relevant to report the number of primary photons detected to compare sensitivity.…”
Section: Discussionsupporting
confidence: 84%
“…Still, almost 25 times more activity is expected to be administered with 212 Pb compared to 223 Ra therapy, and it is therefore expected that images of reasonable quality can be obtained. Count rates with 227 Th and 225 Ac were lower than with 223 Ra and hence also lower than with 212 Pb [13]. Other studies have attempted to quantify 227 Th and 223 Ra in combination with planar imaging and found that 227 Th can be separated from 223 Ra in the images.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a study by Benabdallah et al. showed POP was used to mimic the vertebra region for quantification accuracy using various theranostic radionuclides in SPECT/CT phantom studies 28 . Hence, further experiments with varying POP thicknesses are required.…”
Section: Discussionmentioning
confidence: 99%
“…27 On the other hand, a study by Benabdallah et al showed POP was used to mimic the vertebra region for quantification accuracy using various theranostic radionuclides in SPECT/CT phantom studies. 28 Hence, further experiments with varying POP thicknesses are required. Our findings suggest that when CT erroneously predicts the skull (made of POP), the activity distribution is underestimated.…”
Section: Discussionmentioning
confidence: 99%